Enhanced electrokinetic remediation of multi-contaminated dredged sediments and induced effect on their toxicity. (August 2019) - Benamar, A.; Tian, Y.; Portet-Koltalo, F.; Ammami, M.T.; Giusti-Petrucciani, N.; Song, Y.; Boulangé-Lecomte, C.
Abstract: Electrokinetic (EK) remediation is often developed for metal decontamination but shows limitations for polycyclic aromatic hydrocarbons (PAHs) and polychlorobiphenyls (PCBs) which are nonionic and involve low aqueous solubility. This paper reports many laboratory studies devoted to the investigations of EK efficiency on the mobility and the removal of metals, PAHs and PCBs from dredged sediments, using a mixture of chelating agent and surfactants. The results showed that increasing chelating agent concentration was favorable for both metal and PAH removal. Applying a periodic voltage gradient associated to a low concentration of additives provided the best removal of Zn, Cd and Pb and also the 16 priority PAHs. The tested fresh harbor sediment was highly resistant to metals and organics mobilization and transport because of an aged contamination, a high buffering capacity, a very low hydraulic permeability and a high organic matter content. However, experiments performed on a former sediment which was deposited many years ago provided better removal results, involving low organic matter and carbonates content. The efficiency of the EK process was also assessed by measuring the acute toxicity of the EK-treated sediment on the copepod Eurytemora affinis exposed to sediment elutriates. Graphical abstract: Image 10882 Highlights: Enhancing additives mixture leads to a better EK remediation of dredged sediments. Increasing chelating agent concentration was favorable for both metal and PAH removal. High organic content and carbonates hinder contaminants removal from the sediment. Sediment electrokinetic treatment induces statistically more toxicity on copepods.